Two new species of the genus Discophorellus Tsaur & Hsu (Hemiptera: Fulgoromorpha: Cixiidae: Cixiini) from Guizhou Province, China - Zhang, Pei; Chen, Xiang-Sheng (Zootaxa, 2011)
Two new species of the Oriental cixiid planthopper genus Discophorellus Tsaur & Hsu, 1991 (Hemiptera: Fulgoromorpha: Cixiidae: Cixiini), D. cehengensis Zhang & Chen sp. nov. and D. transspinus Zhang & Chen sp. nov., from Guizhou Province, southwestern China, are described and illustrated. The generic characteristics are redefined. A key to the three known species of this genus in the world is provided.